Strategic manoeuvering in divergent Zimbabwean parliamentary debates - Jakaza, Ernest; Visser, MW (IGI Global, 2016)
The chapter makes a critical exploration of the Zimbabwean divergent parliamentary debates held after the 'controversial' March 2008 election and June 2008 run- off. Considering the impact of the deliberations in the parliament, not much discourse- linguistic research occurs on Zimbabwean and African parliamentary discourse yet research on language use in the context of the European, Asian and American parliaments is enormous. It is the focus of this chapter to examine the nature of strategic manoeuvering realized in Zimbabwean divergent parliamentary debates. Strategic manoeuvering is evident in divergent debates as interlocutors advance their positions in an effort to resolve a difference of opinion. The researchers argue that participants in divergent debates employ valid and fallacious strategic moves in an effort to clear the difference of opinion and have the debate resolved in their favor